Synthesis and characterization of nanostructured lipid nanocarriers for enhanced sun protection factor of octyl p-methoxycinnamate - Prado, Alice Haddad Do [UNESP]; Araújo, Victor Hugo Sousa [UNESP]; Eloy, Josimar O.; Fonseca-Santos, Bruno [UNESP]; Pereira-Da-Silva, Marcelo A.; Peccinini, Rosângela Gonçalves [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2020)
Sunlight is important to health, but higher exposure to radiation causes early aging of the skin and skin damage that can lead to skin cancers. This study aimed at producing a stable octyl p-methoxycinnamate (OMC)–loaded nanostructured lipid carrier (NLC) sunscreen, which can help in the photoprotective effect. NLC was produced by emulsification-sonication method and these systems were composed of myristyl myristate (MM), caprylic capric triglyceride (CCT), Tween® 80 (TW), and soybean phosphatidylcho-line (SP) and characterized by dynamic light scattering (DLS), zeta potential (ZP) measurement, atomic force microscopy (AFM), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and in vitro release studies. Pre-formulation studies were performed changing TW concentrations and no differences were found at concentrations of 1.0 and 2.0%. Two selected formulations were designed and showed an average size of 91.5–131.7, polydispersity index > 0.2, and a negative value of ZP. AFM presented a sphere-like morphology and SEM showed ability to form a thin film. DSC exhibited that the incorporation of OMC promoted reduction of enthalpy due to formation of a more amorphous structure. Drug release shows up to 55.74% and 30.57%, and this difference could be related to the presence of SP in this formulation that promoted a more amorphous structure; the release mechanism study indicated Fickian diffusion and relaxation. Sun protection factor (SPF) evaluation was performed using NLC and presented values around 40, considerably higher than those observed in the literature. The developed formulations provide a beneficial alternative to conventional sunscreen formulations.
Keywords: Drug release; DS: Octyl p-methoxycinnamate; Nanostructured lipid carrier; Sun protection factor; Sunscreen